1993
DOI: 10.1007/bf01976222
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diclofenac and ketoprofen on halothane MAC in rabbit

Abstract: Non-steroidal anti-inflammatory drugs obviously act also on the central nervous system. We, therefore, studied the effect of diclofenac 3 mg/kg and ketoprofen 4 mg/kg on the minimum alveolar concentration (MAC) of halothane in 10 New Zealand White rabbits. After determination of halothane MAC, total doses of NSAIDs were administered intravenously as three subdoses: 12.5%, 37.5% and 50% of the total dose. Depth of anaesthesia did not increase significantly after the first two doses with either drug. With ketopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Wide individual variability and inconsistent effects of dose on anesthetic MAC have been shown for NSAIDs (Rorarius et al. 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Wide individual variability and inconsistent effects of dose on anesthetic MAC have been shown for NSAIDs (Rorarius et al. 1993).…”
Section: Discussionmentioning
confidence: 99%
“…14 In mammals 15,16 and birds, 17,18 for instance, studies have shown that opioids reduce the requirement for inhalant anesthetics during anesthesia. However, NSAID have not been shown to reliably reduce the MAC of inhalant anesthetics in mammals or birds 16,17,19 ; therefore, we did not evaluate the effects of ketoprofen on the MAC of isoflurane in these birds.…”
mentioning
confidence: 99%